2022
DOI: 10.3390/cli10060082
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Geographical Information Systems and the Analytic Hierarchy Process in Selecting Sustainable Areas for Urban Green Spaces: A Case Study in Hue City, Vietnam

Abstract: In recent years, there has been growing awareness about the roles and benefits of urban green spaces (UGSs), particularly in the context of mitigating the negative effects of climate change, which have become increasingly serious. In Vietnam, the government has allocated considerable resources to the development of UGSs in many cities. However, regarding implementation, UGS development in Vietnam faces many challenges; many cities find it difficult to meet the set criterion regarding the number of green spaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…It has been reported that the development of urban areas, particularly in new residential areas, has invaded a large green area in Da Nang and created a negative impact on the environment (Do et al, 2018 ), particularly due to the expansion of built-up areas since the late 1990s (Huong et al, 2022 ) by logging down a large number of forest and shrubland areas (Linh et al, 2009 ). The second study site, Hue City, is known as one of the greenest cities in the country, and a number of areas suitable for urban green spaces as this imperial citadel area is managed and conserved under the heritage conservation law of Vietnam and building new structures in the protected areas is prohibited (Linh et al, 2022 ). However, the rise in population growth and tourism in Hue have caused deterioration of green spaces (Dinh & Pham, 2021 ), which is evident from NDVI and LST maps derived from the present study.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the development of urban areas, particularly in new residential areas, has invaded a large green area in Da Nang and created a negative impact on the environment (Do et al, 2018 ), particularly due to the expansion of built-up areas since the late 1990s (Huong et al, 2022 ) by logging down a large number of forest and shrubland areas (Linh et al, 2009 ). The second study site, Hue City, is known as one of the greenest cities in the country, and a number of areas suitable for urban green spaces as this imperial citadel area is managed and conserved under the heritage conservation law of Vietnam and building new structures in the protected areas is prohibited (Linh et al, 2022 ). However, the rise in population growth and tourism in Hue have caused deterioration of green spaces (Dinh & Pham, 2021 ), which is evident from NDVI and LST maps derived from the present study.…”
Section: Resultsmentioning
confidence: 99%
“…This information was obtained from the literature review and refers to spatial data. -Public opinion in terms of accessibility to green spaces [21], which was obtained through discussion with a focus group. This focus group served as a panel to obtain from the inhabitants their understanding of the conditions leading to green space installation for potential use.…”
Section: Data Collection Dealing With the Identification Of Appropria...mentioning
confidence: 99%
“…Various studies have been carried out on identifying suitable sites for green spaces, combining environmental and social factors in the hierarchical multi-criteria analysis process [21,24,27]. In such an approach, the number of factors and the resulting criteria vary according to the theme and the study area [28].…”
Section: Identification and Description Of Suitable Factors Of Which ...mentioning
confidence: 99%
See 2 more Smart Citations